(untitled) (Aporte Santiaguino, 2023)
The use of biophilic architecture improves the habitable space of users through the connection between the built environment and nature, which is why the study focused on determining what influence the application of biophilic architecture generates in the design of a residential center for the elderly in the district of Hualmay 2023. The methodology that was applied in this research is a basic no experimental design with descriptive scope. The results obtained after applied a questionary to the 74 elderly people, that consist in the sample of the study, allowed to determine the positive influence that was generated by using the criteria of the biophilic architecture into the design of the residential center. Where 91,9% of the surveyed pointed out that for the space comfort dimension would obtain a high level of benefits, and the 95,9% of the participants considered that there would be a great level of benefits in relation to the services dimension. The study concluded that the application of biophilic architecture would have a positive influence in the design of the residential center, by generating benefits in the perception of the building spaces, that would improve comfort, experience, and wellbeing of the elderly.